Occurrence of Pharmaceuticals and Other Anthropogenic Compounds in the Wastewater Effluent of Arctic Expedition Cruise Ships - van der Schyff, Veronica; Stiborek, Marek; Šimek, Zdeněk; Vrana, Branislav; Meraldi, Verena; King, Andrew Luke; Melymuk, Lisa (Environmental science & technology letters, 2025)
Cruise ship traffic in polar regions is increasing, but we lack a good understanding of the emissions from these ships to sensitive marine environments. Wastewater discharges may result in the release of contaminants of emerging concern into such environments. Treated wastewater from three expedition cruise ships was collected and analyzed with a focus on pharmaceuticals, personal care products, and industrial chemicals. Samples were screened using data-dependent acquisition using liquid chromatography-high-resolution mass spectrometry (LC-HRMS). More than 160 compounds were identified at Schymanski level 1 or 2 (SL1 or SL2, respectively) in treated wastewater across all three ships. Twenty-seven compounds were identified in wastewater from all three ships, suggesting their potential wider presence in ship wastewater and warranting further investigation. For all ships, pharmaceuticals dominated in terms of the number of compounds identified at SL1 or SL2 (43-59%), primarily cardiovascular medications, followed by industrial chemicals (21-31%) and natural compounds (12-17%). Multiple antibiotics were identified at SL1, raising concerns that ship wastewater effluent could contribute to the undesired spread of antibiotic-resistance genes. With the ongoing growth of the cruise industry and uncertainties related to impacts on sensitive marine environments, further investigation of ship wastewater emissions is recommended.